2021
DOI: 10.1007/s42452-021-04450-6
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of graphite and titanium oxide powder mixed dielectric for electric discharge machining of Ti–6Al–4V

Abstract: Ti–6Al–4V is the most commonly used titanium alloy in aerospace, marine, and biomedical applications. Due to the properties of poor machinability in conventional machining, Electrical Discharge Machining (EDM) is considered a prospective alternative for machining this strategic material. This study aims at enhancing the performance of powder mixed EDM (PMEDM) in the machining of Ti–6Al–4V with the application of two different types of powders, namely Graphite (Gr) and Titanium Oxide (TiO2) powders, with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The modification on a PM-EDMed surface can be evidenced in the form of a noticeably thick recast layer exhibiting upgraded surface properties such as improved surface integrity, micro-cracks, corrosion resistance, wear resistance, and biocompatibility [ 214 , 215 ]. In the case of PM-EDM of Ti and Ti alloys, B 4 C [ 216 ], surfactant, graphite, TiO 2 [ 217 , 218 ], SiC, Al 2 O 3 [ 219 222 ], Si [ 223 ], and carbon nanotubes (CNTs) [ 224 ] powder particles were primarily used. For instance, with variation in the powder characteristics (particle sizes and concentrations) of SiC and Al 2 O 3 powders and dielectric mediums (such as EDM oil, deionized water, and tap water), considerable changes in the surface roughness (SR), recast layer thickness (RLT), material subtraction/removal rate (MRR), and tool wear rate (TWR) were witnessed [ 225 227 ].…”
Section: Surface Modification Of Metallic Implant Biomaterialsmentioning
confidence: 99%
“…The modification on a PM-EDMed surface can be evidenced in the form of a noticeably thick recast layer exhibiting upgraded surface properties such as improved surface integrity, micro-cracks, corrosion resistance, wear resistance, and biocompatibility [ 214 , 215 ]. In the case of PM-EDM of Ti and Ti alloys, B 4 C [ 216 ], surfactant, graphite, TiO 2 [ 217 , 218 ], SiC, Al 2 O 3 [ 219 222 ], Si [ 223 ], and carbon nanotubes (CNTs) [ 224 ] powder particles were primarily used. For instance, with variation in the powder characteristics (particle sizes and concentrations) of SiC and Al 2 O 3 powders and dielectric mediums (such as EDM oil, deionized water, and tap water), considerable changes in the surface roughness (SR), recast layer thickness (RLT), material subtraction/removal rate (MRR), and tool wear rate (TWR) were witnessed [ 225 227 ].…”
Section: Surface Modification Of Metallic Implant Biomaterialsmentioning
confidence: 99%
“…Specimens machined with Gr electrode exhibit average Ra value of 2.54 μm, and it was increased to 2.65 μm and 2.87 μm when machined with Br and Cu electrode, respectively. Because of the Cu electrode's superior thermal conductivity, very high intensity heat was generated, causing deeper craters and cracks to develop on the machined face, resulting in higher Ra value than a Br-machined specimen [49]. When machined with Gr electrode, as the majority of heat was passed to the tool material, the work piece was subjected to low spark, resulting in improved surface quality.…”
Section: Influence Of Various Process Parameters On the R A Of Az91mentioning
confidence: 99%
“…The minimal magnitude of TWR is observed with the positive polarity using a copper electrode in a graphene-based slurry. Alam et al [1] investigated the performance of power mixed EDM in the machining of Ti-6Al-4V in terms of MRR and TWR. The study adopted surface response methodology to investigate the influence of process parameters including peak current, powder type, and powder concentration on MRR, TWR.…”
Section: References Process Used Workpiece Materials Tool Materialsmentioning
confidence: 99%
“…These characteristics are very important components performance, durability, and reliability. Many research studies were published to investigate the use of the EDM technique in surface treatment, and found that the surface was improved [1,27,47].…”
Section: Surface Integritymentioning
confidence: 99%
See 1 more Smart Citation